What Kind of Connection Exists Between Marketing Attitudes and Behaviour? A Peep into the Interacting Landscape of the Marketing and LIS World - Singh, Rajesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper attempts to find if there is any connection between the marketing attitudes and behaviour of librarians in thirty-three different libraries of Finland. Based on market-oriented behaviour, three kinds of libraries were found: strong, medium and weak. The findings indicate a positive relation between the marketing attitudes and behaviour. Cet article tente de déterminer s’il existe un lien entre l’attitude marketing et le comportement des bibliothécaires de trente-trois bibliothèques différentes de Finlande. S’appuyant sur le comportement axé sur le marketing, trois catégories de bibliothèques ont été recensées : fortes, moyennes et faibles. Les résultats indiquent une corrélation positive entre l’attitude marketing et le comportement.